On the McKean–Vlasov equation with infinite mass - Tantsiura, M. V. (Reports of the National Academy of Sciences of Ukraine, 2016)
We consider infinite systems of stochastic differential equations that describe the motion of interacting particles in a random environment. Theorems on existence and uniqueness of the solution are proved. We also obtain a limit theorem for corresponding measure-valued processes in the case where the mass of each particle tends to zero, and the density of particles grows to infinity.